2008
DOI: 10.1517/14728222.12.5.605
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of extracellular proteases required for the progression of pancreatic cancer

Abstract: Background : Pancreatic ductal adenocarcinoma (PDA) is the fourth leading cause of cancer-related death in the United States. Its lethality is due, in large part, to its resistance to traditional chemotherapeutics. As a result, there is an enormous effort being put into basic research to identify proteins that are required for PDA progression so that they may be specifically targeted for therapy. Objective : To compile and analyze the evidence that suggests that extracellular proteases are significant contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 139 publications
(144 reference statements)
1
2
0
Order By: Relevance
“…We found that angiogenesis genes tended to be significantly downregulated in BRCA (Breast invasive carcinoma) and UCES(Uterine Corpus Endometrial Carcinoma), but upregulated in PAAD (Pancreatic adenocarcinoma), GBM (Glioblastoma multiforme). These findings are consistent with several previous studies (Ardito et al, 2008;Liu et al, 2019). For example, SPP1 was upregulated in most tumor types.…”
Section: Correlations Between Angiogenesis Score and Immunological Genessupporting
confidence: 93%
“…We found that angiogenesis genes tended to be significantly downregulated in BRCA (Breast invasive carcinoma) and UCES(Uterine Corpus Endometrial Carcinoma), but upregulated in PAAD (Pancreatic adenocarcinoma), GBM (Glioblastoma multiforme). These findings are consistent with several previous studies (Ardito et al, 2008;Liu et al, 2019). For example, SPP1 was upregulated in most tumor types.…”
Section: Correlations Between Angiogenesis Score and Immunological Genessupporting
confidence: 93%
“…The recognition of MMPs as disease biomarkers has stimulated the development of imaging strategies targeting these proteases, aiming for improved diagnosis or application in image-guided surgery. Commonly used approaches for MMP imaging are based on targeting with antibodies or smallmolecule ligands (5)(6)(7)(8)(9). For example, radiolabeled MMP binding ligands have been developed for the detection of upregulated MMP levels by means of SPECT or PET (10)(11)(12).…”
mentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) has a relevant physiological function regulating epithelial tissue development. Aberrant activation of EGFR plays a key role in PC through the activation of downstream cascades that promotes cell survival and proliferation [ 7 , 8 ]. One of the most important EGFR-downstream protein is the focal adhesion kinase (FAK).…”
Section: Introductionmentioning
confidence: 99%